Via New York - Pincus-Witten, Robert; Evans-Clark, Phillip (Montréal : Musée d'Art Contemporain, 1984)
Africano, Nicholas ; Baselitz, Georg ; Basquiat, Jean-Michel ; Brown, James ; Chia, Sandro ; Clemente, Francesco, ; Cucchi, Enzo ; Di Rosa, Hervé ; Ferrer, Rafael ; Fischl, Eric ; Gilbert & George ; Haring, Keith ; Immendorff, Jörg ; Kiefer, Anselm ; Lüpertz, Markus ; Mariani, Carlo Maria ; Morris, Robert ; Paladino, Mimmo ; Penck, A.R. ; Salle, David ; Scharf, Kenny ; Schnabel, Julian ; Sultan, Donald ; Winters, Terry
Via New York, Musée d'Art Contemporain, Montréal, 8 mai - 24 juin 1984
boek